TYPE OF AUTHOR-ARTIST IN TEXTS OF KYIV SCHOOL OF POETS - Derkachova, O. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The main type of the author in the texts of the poets of Kyiv school is described in the article. It is a type of author-artist, which desires to put in order the world, creates other, change the primitive values of concepts, and also defines bases of the universe by means of word.